A study on the determinants of customer loyalty using electronic banking website in Seremban, N.Sembilan / Nur Aisyah Jasni - Jasni, Nur Aisyah (2015)
Project paper titled “STUDY ON THE DETERMINANT OF CUSTOMER LOYALTY USING ELECTRONIC BANKING WESBITE IN SEREMBAN, N.SEMBILAN.” is conducted as partial requirement to fulfill the requirement as needed by the faculty of Business Management, Universiti Teknologi Mara (UITM). The intention of this study is to determine the relationship between dependent variable, customer loyalty and independent variables; privacy and security, ease of use and accessibility well as to identify the most influential factor that contributes customer on using electronic banking website in N.Sembilan. Data used in this research are primary and secondary data such as journal and books. Researcher also use questionnaire to attain the data in order to get the feedback from the user of e-banking website. The sample size in this research is 100 respondents user of e-banking from Seremban, N.Sembilan. Based on reliability test, respondent demographic, frequency, Pearson correlation and multiple regressions, a clear findings and result is observed. The finding showed that customer loyalty has positive correlation with privacy and security, ease of use and accessibility. Privacy and security factor has the highest correlation with customer loyalty. The researchers also provide some recommendations and suggestion for future research and also on how to improve e-banking services after analysis, findings and interpretation is done. The conclusion of this study was the outcome from the survey analysis and findings.